2012
DOI: 10.1111/j.1472-765x.2012.03288.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular responses of Salmonella Typhimurium to antimicrobial-induced stresses during the planktonic-to-biofilm transition

Abstract: Aim:  To characterize the cellular and molecular properties of Salmonella Typhimurium exposed to antimicrobials in association with physicochemical property, biofilm formation ability and gene expression patterns. Methods and Results:  The antimicrobial susceptibilities against Salmonella Typhimurium were evaluated to determine the MICs of allyl isothiocyanate (AITC), thymol, eugenol and polyphenol. Cell surface hydrophobicity, aggregation and biofilm formation assays were conducted to assess the physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
(67 reference statements)
2
14
0
3
Order By: Relevance
“…These authors found that trans -cinnamaldehyde was able to mitigate autoinducer 2 based quorum sensing and biofilm formation without inhibiting bacterial growth, probably due to its effect on gene transcription. Similar transcription modulatory effects have been observed in other major pathogens such as Salmonella [108] and P. aeruginosa [109] following exposure to PDAs. Since quorum sensing is one of the key processes involved in cell-to-cell communication and social behavior in microbes, the aforementioned reports could provide new insights into the development of novel therapeutics targeting key physiological processes in microbes.…”
Section: Critical Antimicrobial Properties Of Pdassupporting
confidence: 70%
“…These authors found that trans -cinnamaldehyde was able to mitigate autoinducer 2 based quorum sensing and biofilm formation without inhibiting bacterial growth, probably due to its effect on gene transcription. Similar transcription modulatory effects have been observed in other major pathogens such as Salmonella [108] and P. aeruginosa [109] following exposure to PDAs. Since quorum sensing is one of the key processes involved in cell-to-cell communication and social behavior in microbes, the aforementioned reports could provide new insights into the development of novel therapeutics targeting key physiological processes in microbes.…”
Section: Critical Antimicrobial Properties Of Pdassupporting
confidence: 70%
“…Although several studies reported that AITC was effective against various foodborne pathogens such as Escherichia coli O157:H7, L. monocytogenes, S. Typhimurium, Bacillus cereus, Staphylococcus aureus and Campylobacter jejuni, in vitro (Dufour et al, 2012;Lin, Kim, Du, & Wei, 2000;Shin, Harte, Ryser & Selke, 2010;Siahaan et al, 2013;Zou et al, 2013;Zou, Woo & Ahn, 2012) or in meat products including ground beef, fresh chicken, fermented sausage and Westphalian ham (Chacon, Muthukumarasamy, & Holley, 2006;Graumann & Holley, 2009;Luciano & Holley, 2009;Nadarajah, Han, & Holley, 2005), its high volatility, strong odor, poor water solubility and reactions with naturally occurring food nucleophiles limit its application in food systems (Chacon et al, 2006;Kim, Chung, Shin, Yam, & Chung, 2008). AITC is unstable in aqueous solution and is easily decomposed to new compounds, particularly under alkaline conditions or at elevated temperature (Ohta, Takatani, & Kawakishi, 1995;Tsao, Yu, Friesen, Potter, & Chiba, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha demostrado que las aves de corral contaminadas con Salmonella aumentan entre 15 y 30% después del procesamiento, como consecuencia de la presencia de bacterias en las superficies en contacto con alimentos 38 . Pero una de las grandes preocupaciones en la industria alimentaria es que en las infecciones asociadas a biopelículas hay una alta Infectología al Día tolerancia a las condiciones de estrés y un aumento del potencial de virulencia de las bacterias 39 . Al respecto, se ha observado que el uso de concentraciones sub-letales de antimicrobianos o la exposición a condiciones estresantes sub-letales, induce a un incremento en la virulencia de las bacterias sobrevivientes (mayor capacidad invasora a células epiteliales humanas e inducción de apoptosis en macrófagos), teniendo éstas un alto potencial infeccioso en caso de entrar en contacto con un hospedero 40 .…”
Section: Las Biopelículasunclassified
“…Al respecto, se ha observado que el uso de concentraciones sub-letales de antimicrobianos o la exposición a condiciones estresantes sub-letales, induce a un incremento en la virulencia de las bacterias sobrevivientes (mayor capacidad invasora a células epiteliales humanas e inducción de apoptosis en macrófagos), teniendo éstas un alto potencial infeccioso en caso de entrar en contacto con un hospedero 40 . En ensayos de supervivencia en S. Typhimurium, se observó que la respuesta molecular al estrés juega un papel importante en la patogenicidad, ya que la formación de biopelículas aumentó entre 89 y 100% después de la exposición a concentraciones sub-letales de polifenoles, permitiendo el incremento de la resistencia a antimicrobianos y su virulencia 39 . La explicación a este comportamiento es un aumento en la expresión de genes involucrados en adhesión a células epiteliales, virulencia y eflujo de sustancias antimicrobianas.…”
Section: Las Biopelículasunclassified
See 1 more Smart Citation